Reconsidering Legal Protections for Child Marriage Victims: A Maqasid Shariah Perspective - Sarib, Suprijati; Niode, Olha S.; Suleman, Nenden Herawaty; Usup, Djamila (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This study aims to analyze the legal protection of victims of domestic violence (KDRT) that occurs due to underage marriage in North Sulawesi through the perspective of Maqasid Sharia. The research method used is qualitative with a juridical-empirical approach, collecting data through in-depth interviews with victims of domestic violence, law enforcement officials, and religious leaders, as well as document analysis from related institutions. The results of the study show that the implementation of legal protection for victims of domestic violence in child marriage is still weak due to social stigma, lack of training of officials, and low public legal literacy. The Maqasid Sharia approach emphasizes the protection of individual souls, intellect, and honor as the main principles for handling domestic violence cases in child marriage. This study recommends increasing legal awareness, training on gender issues for officials, and strengthening cross-agency collaboration to create a more effective protection system. These findings are expected to enrich the literature and contribute to the development of policies for the protection of victims of domestic violence in Indonesia.